Clostridioides difficile Colonization Is Differentially Associated With Gut Microbiome Profiles by Infant Feeding Modality at 3–4 Months of Age - Drall, Kelsea M.; Tun, Hein M.; Morales-Lizcano, Nadia P.; Konya, Theodore B.; Guttman, David S.; Field, Catherine J.; Mandal, Rupasri; Wishart, David S.; Becker, Allan B.; Azad, Meghan B.; Lefebvre, Diana L.; Mandhane, Piush J.; et al. (Frontiers in Immunology, 2019)
Colonization with Clostridioides difficile occurs in up to half of infants under the age of 3 months, is strongly influenced by feeding modality and is largely asymptomatic. In spite of this, C. difficile’s presence has been associated with susceptibility to chronic disease later in childhood, perhaps by promoting or benefiting from changes in infant gut microbiome development, including colonization with pathogenic bacteria and disrupted production of microbial bioactive metabolites and proteins. In this study, the microbiomes of 1554 infants from the CHILD Cohort Study were described according to C. difficile colonization status and feeding mode at 3-4 months of age. C. difficile colonization was associated with a different gut microbiome profile in exclusively breastfed (EBF) versus exclusively formula fed (EFF) infants. EBF infants colonized with C. difficile had an increased relative abundance of Firmicutes and Proteobacteria, decreased relative abundance of Bifidobacteriaceae, greater microbiota alpha-diversity, greater detectable fecal short chain fatty acids (SCFA), and lower detectable fecal secretory Immunoglobulin A (sIgA) than those not colonized. Similar but less pronounced differences were seen among partially breastfed infants (PBF) but EFF infants did not possess these differences in the gut microbiome according to colonization status. Thus, breastfed infants colonized with C. difficile appear to possess a gut microbiome that differs from non-colonized infants and resembles that of EFF infants, but the driving force and direction of this association remains unknown. Understanding these compositional differences as drivers of C. difficile colonization may be important to ensure future childhood health.